Análise do Desempenho de poços de infiltração na cidade de Goiânia-GO - ARAUJO, Alexandre Garces de (2010)
This paper presents the performance study of infiltration pits. Two experimental fields were selected for evaluation of the pits, one studied by Carvalho (2008) and the other deployed in this work. The main objective of this research is to evaluate the sensitivity of the performance of the infiltration pit before the variability of soil properties. Three performance parameters were considered: time of infiltration 50%, 70% 85% the volume of water in the well. The variability of the properties was made with the use of possible values obtained by the coefficient of variation of each property evaluated. In the experimental field deployed in this study were collected undisturbed samples to perform laboratory tests such as characterization, consolidation test method, soil-water characteristic curve, saturated and unsaturated hydraulic conductivity. The SWCC showed the presence of macro structure and its format as bimodal. The saturated hydraulic conductivity showed that the soil behavior is governed by the macro structure, this resulted in hydraulic conductivity value close to the sandy. The hydraulic conductivity test was performed at the Federal University of Rio Grande do Sul using the permeameter developed by Feuerharmel (2007). The function of hydraulic conductivity obtained was compared with Brooks & Corey (1964) prediction method showing good results to the first baseline of SWCC. An automated method was developed for monitoring the variation of the water column in the well during infiltration. The method was based on the use of pressure sensors and a data acquisition system, comparing this method with using a conventional tape measure showed good results. Numerical analysis showed that the saturated hydraulic conductivity is the property that most influence on the performance of the structures of infiltration differences were not observed in the analysis considering different depth of groundwater level.